Model-Free Identification of Hysteretic Restoring-Force Characteristic of Multi-Plane and Multi-Story Frame Model With In-Plane Flexible Floor - Shintani, Kenichirou; Yoshitomi, Shinta; Takewaki, Izuru (Frontiers in Built Environment, 2020)
While linear system identification (SI) has been developed extensively, research advancement in the field of nonlinear hysteretic SI is not satisfactory. An innovative method of identification of hysteretic restoring-force characteristics is proposed in this paper for three-dimensional (3D) building structures with in-plane flexible floors. The hysteretic restoring-force characteristics of vertical structural frames in the 3D building structure are identified from the measured floor horizontal accelerations together with the hysteretic restoring-force characteristics of floors without the assumption of hysteresis types or a priori knowledge of restoring force characteristics. Fourier expansion is applied to the time-history responses of story shear forces in vertical frames and in-plane shear forces in horizontal frames (floors). It is shown that a batch processing least-squares estimation method for many discrete time-domain measured data enables the direct identification of the Fourier coefficients on the story shear forces in vertical structural frames and those on the in-plane shear forces in floors. The proposed method is simple and direct because only Fourier expansion and batch processing least-squares estimation are required. Numerical simulations using measured data without noise and measured data with noise are conducted for investigating the accuracy and reliability of the proposed method. It is demonstrated that the proposed method can identify successfully the hysteretic restoring-force characteristics of plane frames in 3D building structures with in-plane flexible floors.